2017
DOI: 10.1039/c6ta09161j
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar nitrogen-doped graphene frameworks as high-performance cathodes for lithium ion batteries

Abstract: As cathode materials in lithium ion batteries, nitrogen-doped graphene frameworks (N-GFs) manifest excellent specific capacity and cycle stability, owing to the fast surface faradaic reactions of pyridinic N and pyridinic N-oxide with both p- and n-doped states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…For NC@GF‐600 electrodes, the values of the charge‐transfer resistance ( R ct ) and ohmic resistance ( R f ) were 50.32 and 0.01 Ω, respectively, which are significantly lower than those of NC@GF‐500 (60.24 and 0.03 Ω) and NC@GF‐700 (69.95 and 0.02 Ω). This result confirmed that the 3D graphene framework coupled with ultrathin carbon‐coating layer containing high‐level pyridinic N should be responsible for the high conductivity of NC@GF‐600 and thus greatly enhance the rapid electron/ion transportation during the electrochemical lithium insertion/extraction reaction …”
Section: Resultsmentioning
confidence: 52%
“…For NC@GF‐600 electrodes, the values of the charge‐transfer resistance ( R ct ) and ohmic resistance ( R f ) were 50.32 and 0.01 Ω, respectively, which are significantly lower than those of NC@GF‐500 (60.24 and 0.03 Ω) and NC@GF‐700 (69.95 and 0.02 Ω). This result confirmed that the 3D graphene framework coupled with ultrathin carbon‐coating layer containing high‐level pyridinic N should be responsible for the high conductivity of NC@GF‐600 and thus greatly enhance the rapid electron/ion transportation during the electrochemical lithium insertion/extraction reaction …”
Section: Resultsmentioning
confidence: 52%
“…This suggests significant redox contribution from the GA radical sites [48] and N-doped centers. [68] The fraction of the diffusion-limited current, most likely linked to the redox process from GA surfaces, decreased to 30% when the scan rate increased to 2.0 mV s −1 (Figure 3d). The same analysis performed for a freshly assembled half-cell (Figure S12a-c, Supporting Information) showed similar electrochemical performance but with a higher fraction of diffusion-limited processes at each potential sweep rate.…”
Section: Resultsmentioning
confidence: 99%
“…The first one corresponds to lithiation-delithiation of the sp 2 graphene moieties of GA. The second is a typical region for carboxylate redox reactions; [9] the third could be regarded as redox-processes involving nitrogencontaining graphene moieties [68] introduced during the synthesis (Figures S3 and S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical measurements revealed that the cathode can deliver a high reversible capacity of 146 mAh g −1 at 50 mA g −1 after 10 0 0 cycles. Moreover, Feng et al prepared the bipolar N-doped graphene frameworks as the cathode for LIBs [115] , and the cathode exhibits an extremely high specific capacity of 379 mAh g −1 at 0.5 A g −1 for 2500 cycles. This performance is superior to most of the reported LIBs cathode materials.…”
Section: Secondary Batteriesmentioning
confidence: 99%